Transfer of the bacterial gene for cytosine deaminase to mammalian cells confers lethal sensitivity to 5-fluorocytosine: a negative selection system. - Mullen, C A (1992)
Expression of the bacterial gene for cytosine deaminase (CD; EC 3.5.4.1) in mammalian cells was evaluated as a negative selection system or suicide vector for potential use in gene transfer studies and therapies. Mammalian cells, unlike certain bacteria and fungi, do not contain the enzyme CD and do not ordinarily metabolize cytosine to uracil. Nor do they metabolize the innocuous compound 5-fluorocytosine to the highly toxic compound 5-fluorouracil. The Escherichia coli CD gene underwent PCR oligonucleotide-directed mutagenesis to enhance its expression in a eukaryotic system and it was then cloned into an expression vector, pLXSN, that also contains a neomycin-resistance gene. Murine fibroblast lines were transfected with the plasmid and subjected to brief selection in the neomycin analogue G418. Lysates from these cell populations exhibited significant CD activity detected by conversion of radiolabeled cytosine to uracil. In clonogenic assays transfected cells expressing CD were selectively killed by incubation in 5-fluorocytosine, whereas control cell lines were not. Dose-response studies evaluating [3H]thymidine incorporation or cloning efficiency demonstrated profound inhibition at and above 65 micrograms of 5-fluorocytosine per ml. Mixed cellular assays showed that CD-positive cells could be eliminated without bystander killing of other cells. Retrovirus-mediated CD gene transfer into various tissues was also demonstrated. Thus CD, with its ability to produce the toxic antimetabolite 5-fluorouracil from 5-fluorocytosine, may be useful as a negative selection system for studies and treatments employing gene transfer techniques.